Analyzing shear band formation with high resolution X-ray diffraction. (1st April 2018) - Pagan, Darren C.; Obstalecki, Mark; Park, Jun-Sang; Miller, Matthew P.
Abstract: Localization of crystallographic slip into shear bands during uniaxial compression of a copper single crystal is studied using very far-field high-energy diffraction microscopy (vff-HEDM). Diffracted intensity was collected in-situ as the crystal deformed using a unique mobile detector stage that provided access to multiple diffraction peaks with high-angular resolution. From the diffraction data, single crystal orientation pole figures (SCPFs) were generated and are used to track the evolution of the distribution of lattice orientation that develops as slip localizes. To aid the identification of 'signatures' of shear band formation and analyze the SCPF data, a model of slip-driven lattice reorientation within shear bands is introduced. Confidence is built in conclusions drawn from the SCPF data about the character of internal slip localization through comparisons with strain fields on the sample surface measured simultaneously using digital image correlation. From the diffraction data, we find that the active slip direction and slip plane are not directly aligned with the orientation of the shear bands that formed. In fact, by extracting the underlying slip system activity from the SCPF data, we show that intersecting shear bands measured on the surface of the sample arise from slip primarily on the same underlying single slip system. These new vff-HEDM results raise significant questions on the use of surface measurements for slip system activity estimation. Graphical abstract: Image 1